2020
DOI: 10.1002/wcs.1527
|View full text |Cite
|
Sign up to set email alerts
|

Must all signals be evolved? A proposal for a new classification of communicative acts

Abstract: While signals in evolutionary biology are usually defined as “acts or traits that have evolved because of their effect on others”, work on gestures and vocalizations in various animal taxa have revealed population‐ or even individual‐specific meanings of social signals. These results strongly suggest that communicative acts that are like signals with regard to both form and function (meaning) can also be acquired ontogenetically, and we discuss direct evidence for such plasticity in captive settings with rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 122 publications
(186 reference statements)
0
15
0
Order By: Relevance
“…Critical will be evidence about how the gesture signals, the characteristic flexible communication systems of the great apes, actually get acquired. Some theories hold there is an innate repertoire [ 49 ], others that many gestures are interactionally learnt ([ 50 ]; see also [ 51 , 52 ]). The latter would open up the possibility of third-order intentionality (the attempt to get the other to think such-and-such by virtue of the recognition of that attempt, i.e.…”
Section: The Origins Of Intention Recognition In Communication: ‘Cute...mentioning
confidence: 99%
“…Critical will be evidence about how the gesture signals, the characteristic flexible communication systems of the great apes, actually get acquired. Some theories hold there is an innate repertoire [ 49 ], others that many gestures are interactionally learnt ([ 50 ]; see also [ 51 , 52 ]). The latter would open up the possibility of third-order intentionality (the attempt to get the other to think such-and-such by virtue of the recognition of that attempt, i.e.…”
Section: The Origins Of Intention Recognition In Communication: ‘Cute...mentioning
confidence: 99%
“…This is precisely the pattern one would expect if pointing is subject to variation in individual learning experiences-the greater the exposure of apes to human engagement, the greater the number of opportunities for animals to be rewarded for successfully deploying pointing, in accordance with long-established psychological principles of behavioral expression. Note that this perspective on the origins and maintenance of pointing in great apes and humans is not a general model for gesture origins in these species, but an account of how pointing, long considered a hallmark of human communication, emerges so easily in our nearest living relatives (for a range of theoretical discussion on the origins of gestures, per se: see, e.g., Bard et al, 2019;Byrne et al, 2017;Fröhlich & van Schaik, 2020;Tomasello & Call, 2007). The essential point, here, is that pointing by great apes is massively variable in its incidence in different populations of great apes, and this variability cannot be explained by appeal to genetic variance, because wild apes, who almost never point, and captive apes, who frequently point, are all sampled from the same gene pools (Leavens, 2004;Leavens, Bard, & Hopkins, 2010).…”
Section: The Referential Problem Spacementioning
confidence: 99%
“…However, accumulating evidence suggests that the socio-ecological environment can profoundly impact the use of communicative signals throughout primate lifetimes (for reviews see Fro ¨hlich Liebal et al, 2013;Snowdon and Hausberger, 1997). For example, recent research on great apes, our closest living relatives, has shown that some gestures and sounds are apparently innovated and maintained over time (Fro ¨hlich et al, 2016;Halina et al, 2013;Hardus et al, 2009b;Hopkins et al, 2007;Tomasello et al, 1997;Wich et al, 2012;Wich et al, 2009), and play the same role in the communication process as evolved signals do-we could thus call them signal innovations (Fro ¨hlich and van Schaik, 2020). This work therefore suggests that it may be timely to distinguish between innate animal signals and those that are acquired developmentally (see Bard et al, 2014 for a similar conclusion, finding that some gestures are clearly genetically predisposed, whereas others are not).…”
Section: Introductionmentioning
confidence: 99%